2020
DOI: 10.1093/ageing/afaa139
|View full text |Cite
|
Sign up to set email alerts
|

Importance of previous hospital stays on the risk of hospital re-admission in older adults: a real-life analysis of the PAERPA study population

Abstract: Background consideration of the first hospital re-admission only and failure to take account of previous hospital stays, which are the two significant limitations when studying risk factors for hospital re-admission. The objective of the study was to use appropriate statistical models to analyse the impact of previous hospital stays on the risk of hospital re-admission among older patients. Methods an exhaustive analysis of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In older adults, the rate of hospital readmission 1 month after the initial discharge can vary from 10% to 24%, depending on the type of readmission and the patient's characteristics (age, comorbidities, frailty, etc) 8 . Hospital readmission is associated with an elevated risk of subsequent hospital readmissions and death 8–10 …”
Section: Introductionmentioning
confidence: 99%
“…In older adults, the rate of hospital readmission 1 month after the initial discharge can vary from 10% to 24%, depending on the type of readmission and the patient's characteristics (age, comorbidities, frailty, etc) 8 . Hospital readmission is associated with an elevated risk of subsequent hospital readmissions and death 8–10 …”
Section: Introductionmentioning
confidence: 99%
“…1,3,4,[6][7][8][9][10][11] We have previously reported that the risks of hospital readmission and death were strongly influenced by the hospital readmission process. 13 However, this analysis was limited by the number of available adjustment variables (ie age, sex, and the CCI). Our present results confirmed the importance of the rank and time to hospital readmission on the change in the risks of hospital readmission and death.…”
Section: Discussionmentioning
confidence: 99%
“…The use of statistical models designed for studying recurrent events is therefore more appropriate when a patient has been admitted to hospital several times. 13 Hospital readmissions should thus be analyzed precisely because they reflect a frequent clinical picture among older adults. Most of the studies of patient pathways in this population have focused on the occurrence of events like hospital readmission or death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Avoidable hospitalisations of older people remain a global challenge for health care systems [1][2][3]. Additionally, the number of unplanned visits to emergency departments (ED) has continued to grow even though many countries have achieved substantial health care improvements in recent decades [4][5][6].…”
Section: Introductionmentioning
confidence: 99%